2018
DOI: 10.1093/ndt/gfy020
|View full text |Cite
|
Sign up to set email alerts
|

Increased urinary osmolyte excretion indicates chronic kidney disease severity and progression rate

Abstract: Renal organic osmolytes, betaine and myo-inositol play a critical role in protecting renal cells from hyperosmotic stress. Kidney tissue transcriptomics of murine preclinical experimentation identified decreased expression of Slc6a12 and Slc5a11 mRNA in renal tissue consistent with defective tubular transport of these osmolytes. Imbalances in renal osmolyte regulation lead to increased renal cell damage and thus more progressive forms of CKD. Increases in renal osmolytes in urine could provide clinical diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 47 publications
3
43
0
Order By: Relevance
“…The bulk of myo-inositol is produced by the kidneys [32]. In CKD, urinary levels of myo-inositol increase due to reduced tubular reabsorption [33]. ADMA is implicated with chronic kidney disease [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The bulk of myo-inositol is produced by the kidneys [32]. In CKD, urinary levels of myo-inositol increase due to reduced tubular reabsorption [33]. ADMA is implicated with chronic kidney disease [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in Clock-mutant mice, Atp1b1 expression was low and blood pressure high [44]. The expression of both NCC and ATP1B1 is altered in kidney injury, potentially linking kidney injury to an altered expression of kidney circadian genes regulating blood pressure [45,46].…”
Section: Chronodisruption In Ckdmentioning
confidence: 99%
“…Inhibition of myo-inositol transport has been shown to cause acute renal failure in rats [62]. Furthermore, it has recently been shown through urine metabolomics profiling of humans that increased levels of myo-inositol are significantly associated with kidney disease and inversely proportional to eGFR [63]. It has also been shown to be elevated in the plasma metabolomic profiles of patients with end-stage renal disease [50,61].…”
Section: Discussionmentioning
confidence: 99%
“…In looking at known perturbations in gene expression levels in AR [14] we observed that the sodium-myo-inositol transporter (SMIT), encoded by SLC5A3, is located in the thick ascending limb and functions to reabsorb myo-inositol into the renal medullary cells under conditions of hypertonicity [64]. Thus, perturbations of this transporter may be a key mechanism for acute rejection related tissue injury, mediated by hyperosmolar stress [63]. Given that patients with AR may have preserved kidney graft function and stable serum creatinine levels, the utility of this biomarker may be confounded given its correlation with eGFR.…”
Section: Discussionmentioning
confidence: 99%